Cu-Doped MnO2 Catalysts for Effective Fruit Preservation via Ozone Synergistic Catalytic Oxidation - Jianguo Huang; Rashid Khan; Chunhui Zhai; Xianting Ding; Li-Sha Zhang; Jin-Ming Wu; Zhizhen Ye (Foods)
Developing and implementing technologies that can significantly reduce food loss during storage and transport are of paramount importance. Ozone synergistic catalytic oxidation (OSCO) technology has been developed, which sterilizes bacteria and viruses on the surface of food and degrades ethylene released during fruit storage through the active oxygen produced by the catalytic decomposition of ozone. Herein, we report the hydrothermal synthesis of MnO2 with distinct phase compositions and nanostructures through simply varying the reaction temperatures. Optimized copper-doped α-MnO2 nanorods exhibited remarkable efficacy in activating ozone at a concentration of 40 ppb, and this activation resulted in the complete eradication of indicator bacteria on food surfaces within a 24 h period. Moreover, these nanorods demonstrated high effectiveness in decomposing more than 80% of the ethylene molecules emitted by apples and bananas during the preservation period. The high concentration of surface oxygen vacancies is believed to contribute to the enhanced catalytic activity of the Cu-doped α-MnO2 catalyst in the OSCO procedure by reducing ethylene production and maintaining the fruit quality during the preservation period.